Evaluation of pulmonary function in children and adolescents with autoimmune rheumatics diseases (Research, Society and Development, 2021)
Objective: To evaluate lung function in patients with juvenile autoimmune rheumatic diseases, as well as describe the main changes found in pulmonary function tests during routine medical consultations. Methodology: Integrative literature review performed in MEDLINE, PubMed, LILACS, Scielo, Cochrane Library and BIREME libraries and databases. Published in the 10-year time frame (June 2011 to June 2021). There will be no restrictions regarding the language, location of the research or year of publication. Duplicate articles, reports with less than 5 cases and editorials will be excluded, in addition to articles that do not meet the aforementioned inclusion criteria. Results: Studies show a high rate of children with pulmonary impairment related to connective tissue disease. Connective tissue disease can result in other complications such as pulmonary arterial hypertension, early detection by transthoracic Doppler echocardiography is essential in the assessment of pulmonary arterial hypertension, being a non-invasive method. Final Considerations: Early detection of pulmonary alterations is essential and can be performed through tests of pulmonary functions and continuous multidisciplinary follow-up, being essential to minimize the impacts of progression and complications of pulmonary diseases.